Gambaran Efek Sevoflurane Terhadap Tekanan Darah pada Pasien General Anestesi - Suyanti Suyanti; Sulastri Sulastri; Vira Aryana Teruruano Malengga (Pusat Riset dan Inovasi Nasional, 2025)
Background: Ceflurane, which is a halogenated ether, is packaged in liquid form, colorless, non-explosive, odorless and non-irritating so it is good for inhalation induction. Research objective: To find out the effect of sevoflurane on blood pressure in patients under general anesthesia. Research Method: The design of this study is a quantitative type using a descriptive approach with a population of 36 people The sample used in this study is purposive sampling with as many as 33 respondents This research was conducted at Ibnu Sina Hospital,Gresik Regency during February-May 2024. The variable in this study is an overview of the effect of sevoflurane on blood pressure. results: An overview of the effect of sevoflurane on blood pressure showed that of the 33 respondents, they had a blood pressure of 15 minutes after being given sevoflurane with an average of 113.36, a median of 114.00, a standard deviation of 10.977 with the blood pressure of general patients after being given sevoflurane at least 93 mmHg and a maximum of 140 mmHg. Conclusion: Based on the study, the picture of the effect of sevoflurane on blood pressure in general anesthesia patients decreased.